A cross sectional study on awareness and prevalence of tobacco use among adult males of Vanakbara village, Diu district - Solanki, Minaxi N.; Zalavadiya, Dhara; Amratlal, Abhishek (International Journal Of Community Medicine And Public Health, 2024)
Background: Tobacco is used in various forms worldwide. The consumption of each pattern is different by the geographic area, economic status, socio-cultural and religious influence. The tobacco problem in India is more complex than that of any other country in the world, with a significant number of tobacco-related diseases and deaths. Over the years, India’s position has risen from third largest to the second largest unmanufactured tobacco consuming country in the world. This study's findings will aid in the future planning of tobacco control and prevention in Vanakbara village of Diu district. Methods: Community base cross-sectional study was conducted among adult males of Vanakbara village, Diu district. A study was conducted from September to November 2020, A sample was selected from the population by using a simple random sampling method. Data was collected using a preformed questionnaire. Data was entered in MS excel and analysis was done using statistical software like SPSS. Average, and the percentage considered and the frequency table and graphs were prepared wherever applicable. Results: According to the study, smokeless tobacco use was more prevalent among adult males (56.6%) than smoked tobacco (14.6%). The most common form of smokeless tobacco used was mawa. According to the majority of respondents (44.3%), smoking was started because they believe it aids in concentration at work, followed by their friends. The study revealed that 88.6% of respondents are aware that tobacco consumption leads to oral cancer. Conclusions: Our study indicates that there is an urgent need for taking actions aiming at increasing effectiveness of enforcing applicable tobacco control regulations in fisherman units.